The large crassatellas (Crassatellidae, Bivalvia) from Oligocene beds near Poljšica - Mikuž, Vasja; Čvorović, Božena (Geologija, 2001)
Among larger and better preserved fossil remains from Oligocene beds at Poljšica are also crassatellas. They are relatively frequent but in general poorly preserved. We expected that determination of two large undamaged crassatellas will be simple and reliable. In the literature, however, many very similar forms were found. Without the knowledge of characteristics of valve interiors and revision of all former large Eocene and Oligocene crassatellas in Europe an accurate determination is not possible. The Poljšica specimens were finally attributed to the species Crassatella cf. pseudotumida Benoist, 1911 which the most resembles our crassatellas.